2013
DOI: 10.1097/ajp.0b013e31827eb5e6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Management of Noncancer Pain in Cancer Patients Referred to a Radiotherapy Center

Abstract: In a cancer patients' population referred to a radiotherapy center, the NCP incidence was higher than the CP incidence and NCP intensity was only slightly lower than CP. NCP was significantly pharmacologically undertreated and it was related to a decline in QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
4
12
0
Order By: Relevance
“…Table 1 shows the selected characteristics of the 66 studies from 1994 to 2020 1,4–23,25–67 . Considering the whole period, the weighted mean of negative PMI decreased from 47% to 40%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the selected characteristics of the 66 studies from 1994 to 2020 1,4–23,25–67 . Considering the whole period, the weighted mean of negative PMI decreased from 47% to 40%.…”
Section: Resultsmentioning
confidence: 99%
“…The full text of the remaining 41 hits was examined; and 19 were excluded as not regarding cancer pain and two were excluded because they were qualitative studies. The 20 studies 4–23 that met the inclusion criteria and were included in the current analysis are listed in Table . The flowchart of study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with cancer often present with an underappreciated noncancer pain component. In a study of 903 patients with cancer at a radiotherapy center, the incidence of noncancer pain was higher than the incidence of cancer pain and contributed significantly to the patient's overall pain burden . In this study of patients suffering from both cancer and noncancer pain components, it was more likely that the noncancer pain be uncontrolled than the cancer pain ( P < 0.001).…”
Section: Types Of Cancer Painmentioning
confidence: 75%
“…One-third of cancer patients presented with chronic non-malignant pain at consultation. A handful of studies have reported the prevalence of chronic non-malignant pain in cancer patients, which varied between 2% and 76% [13,14]. This wide variation may be explained by differences in the patient population, definitions, and study methodology.…”
Section: Discussionmentioning
confidence: 99%
“…This wide variation may be explained by differences in the patient population, definitions, and study methodology. Specifically, previous studies were mostly retrospective in nature [14][15][16] and non-malignant pain diagnosis was not the main study outcome [13,17]. Moreover, a majority of studies focused on documenting one main pain site per patient when patients often presented with multiple pain types, which could result in an underestimation.…”
Section: Discussionmentioning
confidence: 99%